Culture-Shaped Language of Male and Female Writers: A Comparative Study of English and Bahasa Indonesia - Irmala Sukendra (Bina Nusantara University, 2021)
The research investigated how the writers of different genders from different cultures (western or American and Asian) reflected the differences in the language they used in their novels. Although gender differences were known to result from cultural differences, less research had been done in terms of contrasting the gender of different cultures, yet to discuss them in terms of gender roles as writers. The research aimed to explore the role of gender in constructing language to examine gender stereotypes from a linguistic perspective and describe gender differences in language use. It applied a qualitative method with library research style, which included several steps of reading the material, collecting and listing the swear words and adjectives used, categorizing the choice of words, and analyzing the choices. The research concludes that culture does contribute to the differences in how swear words are expressed, in which Indonesian writers use fewer swear words and avoid using vulgar words and profanity. In other words, gender differences do not affect adjectives used in bahasa Indonesia.